Collage as subjective experience: Transitioning, relinquishing, becoming. (1st June 2013) - Bell, Alison F.
Through reflexivity and its intrinsic multiple interpretations of the 'image', collage allows one to find the words to express subjective experience. By a practicing artist searching for a method of enquiry through creative practice that seamlessly merges the making and the textual, this article will outline the narrative of a synthesis of the thinking through making and ongoing reflexivity where collage is used as a form of methodology within a practice based Ph.D.